Soil and Water Conservation for Sustainable Crop Production in Kandi region of Jammu - Sanjay Arora; Vikas Sharma; A. Kohli; V.K.Jalali (Journal of Soil and Water Conservation, 2022)
In the kandi region of Jammu, in the Shivalik foothills, it was observed that 92% of the families have cultivable holdings of less than 2 ha. Maize-wheat is dominant crop rotations in the area. Crop yields in this area are quite low and the situation warrants an efficient conservation and management of both land and rainwater, which include in-situ moisture and optimal utilization as per the needs and requirements of crop production systems. Past studies indicate that 4 ploughings are necessary for wheat to get better yield per unit area of land. An increase in soil moisture content from 6.7 % without ploughing to 19.4 % with 4 ploughings has been proved. On-farm experiments with maize in lower Shivaliks, showed that on account of increase in the soil moisture storage of 9.3, 12.7 and 16.8 per cent an increase in the plant height to the tune of 18.1, 33.1 and 49.9 per cent respectively. These studies were carried out using shallow tillage, deep tillage and ridge and furrow treatments respectively over the control. An increase of 10.6 per cent in maize grain yield using ridge and furrow sowing over control has been observed.